Physical Properties and Compactability of Various Blends of Fully Gelatinised and Pregelatinised Maize Starch - Angupale, Jimmy R.; Engeu Ogwang, Patrick; Okafor, Sylvester I. (Pharmaceutical and Biosciences Journal, 2020)
The use of pregelatinised maize starch in direct compression as a sole binder produces tablets with relatively low tensile strength. Fully gelatinised maize starch possesses better binding properties but its use is limited in immediate release tablets. The aim of this work was to prepare a blend of fully gelatinised and pregelatinised maize starch possessing optimum tabletting properties. The pregelatinised starch was prepared by heating a 15 % slurry at 65 ℃ for 15 min followed by filtration and drying. The fully gelatinised starch was prepared by heating a 10 % slurry at 80 ℃ for 5min followed by precipitation with acetone, filtration and drying. The two samples were blended in 100:0, 25:75, 50:50, 75:25 and 0:100 proportions. Both local and BP starch samples were used and their blends compared for flow, packing characteristics and compactability. The disintegration time of the compacts was also determined. The results indicated that the BP starch blends exhibited better tabletting properties compared to the local starch. The proportion with 100 % fully gelatinised starch showed the best flow and compactability.
Keywords: Physical Properties; Pregelatinised Maize Starch; Compactability